Silikat dan Titanium Silikat Mesopori-Mesotruktur Berbasis Struktur Heksagonal dan Kubik - Hari Sutrisno; Retno Arianingrum; Ariswan Ariswan (Jurnal Matematika & Sains, 2005)
Silicalite (MCM-41 & MCM-48) and titanium silicalite (Ti-MCM-41 & Ti-MCM-48) mesoporous-mesostucture material have been synthesized and studied. Its have been obtained from hydrolysis and condensation of reactant : tetraethyl orthosilicate (TEOS) as silicium source and cetyltrimethyl ammonium bromide (CTAB) surfactant as template, NaOH as base and water solution. Ti-MCM-41 & Ti-MCM-48 mesoporous-mesostucture material have been synthesized from crystal of [Ti8O12(H2O)24]Cl8.HCl.7H2O as titanium source. Surfactant was removed by calcinations at 5500C for 5 hours. MCM-41 and Ti-MCM-41 are crystallized on the hexagonal structure, plane group p6 with unit cell parameter: a = 44.09 and 49.48 Çº respectively, meanwhile MCM-48 and Ti-MCM-48 are crystallized on the cubic structure, space group Ia3d with unit cell parameter: a = 87.46 and 94.42 Çº respectively.